Morphometric Analysis of the Supraorbital Foramen/Notch: Prevalence, Anatomical Variations, and Surgical Implications in an Indian Population - Dr S Kalaivani; Dr. Vijayakumar; Dr. P. N. Ruvanthika (The Bioscan, 2026)
Objective: This observational study aimed to determine the prevalence, precise morphometric parameters, and clinical correlations of the supraorbital foramen (SOF) and supraorbital notch (SON) in a sample of dry adult human skulls of Indian origin. Design: A cross-sectional, descriptive osteological study. Sample: One hundred and twenty-eight (n=128) dry, intact, adult human skulls of known Indian origin, obtained from the Department of Anatomy at a tertiary medical institute, providing 256 orbital sides for examination. Methods: The skulls were visually inspected and palpated to categorize each orbital rim as possessing a SOF or SON. Precise measurements were taken using a digital vernier calliper (precision ±0.01 mm). Parameters recorded included: distance from the centre of the SOF/SON to the midline (nasofrontal suture); distance from the superior orbital rim; and the vertical and transverse diameters of the SOF. Asymmetry and bilateral variations were noted. Data were analysed using descriptive statistics and paired t-tests. Results: The SOF was identified in 58.6% of orbital sides, while the SON was present in 41.4%. Bilateral symmetry in form (SOF/SON) was observed in 78.1% of skulls. The mean distance from the midline was significantly greater for SOF (25.1 ± 1.8 mm) compared to SON (24.0 ± 2.2 mm) (p<0.05). The mean distance from the superior orbital rim was 2.3 ± 0.7 mm. Asymmetry in the position (distance from midline differing by >2 mm) was found in 31.3% of skulls. Conclusion: The study documents a high prevalence of the supraorbital foramen in the Indian population, with significant occurrence of positional asymmetry. These findings are critical for preoperative planning in forehead and orbital surgeries, nerve block procedures, and to prevent iatrogenic neurovascular injury. The data provide a population-specific anatomical baseline previously underrepresented in literature. Keywords Supraorbital foramen, Supraorbital notch, Morphometry, Indian population, Osteology, Surgical anatomy, Trigeminal nerve.